New Petro-Mineralogical Results on the Magmatic Surrounding Rocks of Cu-Ag Mineralization in Tagmout (Eastern Anti -Atlas, Morocco) - Moussaid Azizi; Aissa Mohamed; El Azmi Mohammed; Souiri Muhamed; Mezougane Hafid; Kharis Abdel-ali; Zouhair Mohamed (European Scientific Journal, ESJ, 2017)
Tagmout deposit is located in the Eastern Anti-Atlas, about 30 km south of the city of Qalâat Mgouna. It contains Cu-Ag mineralization which is embedded in magmatic rocks that are essentially intrusive of various facies. Detailed mapping (1/1200) and petro-mineralogical observation of these facies allow us to distinguish: 1) Olivine gabronorite, it is composed mainly of pyroxenes (CPX and OPX), olivine and biotite; 2) Quartz monzogabbro, it is characterized by the presence of pyroxenes, amphiboles, plagioclases, FK and quartz; 3) Quartz monzodiorite, which is a porphyric facies. It occupies the center of the Tagmout sector which is rich in FK, plagioclase, quartz, amphibole and pyroxene; 4) Granodiorite, it is a facies associated with quartz monzodiorite. It shows a paragenesis composed of FK, quartz and plagioclase; 5) Pink microgranite, metric dykes developing in different directions (N10° to N15°, N70° to N90°, N120° to N130 °). It is a facies rich in quartz, FK and plagioclase; 6) Dolerite, It is a dark-colored facies with a typical doleritic texture. It is rich in plagioclase and relics of pyroxenes and amphiboles. This facies occupies the eastern part of Tagmout complex; 7) Volcano-sedimentary facies with rhyolite appearance of brick red color. It is a vitreous fine matrix and conglomerate elements which is rich in quartz and FK. These are conglomerates that are affected by the terminal neoproterozoic rhyolitic lavas. They are also affected to different degrees by several phases of hydrothermal alterations of potassic, phyllitic, clayey, and propylitic types. The effect of these alterations on the rock at the surface is very variable. The granodiorite is highly affected while olivine gabbronorite is not very sensitive and retains a remarkable state of freshness. This raises an interrogation on the chronological place and the advanced age for these facies (557 ± 5 Ma, Benziane and al. 2008).With the exception of recent formations (microgranite, dolerite and volcano-sedimentary facies), the contact between the plutonic rocks of Tagmout (olivine gabbronorite, quartz monzogabbro, quartz monzodiorite, granodiorite and granite) never takes major structural discontinuity nor contact metamorphism. But the localization of some enclaves on both sides of the neighboring facies with an intense brecciation marked the contact of these facies. This configuration suggests that the plutonic formations of Tagmout massive that the setting up was done in a contemporary way and is derived from the same magma by fractional crystallization in a magmatic chamber.